Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Kementerian Agama Kota Tangerang Selatan - Feb Amni Hayati; Lili Sularmi; Veritia Veritia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In the context of public sector organizations, improving employee performance is essential to ensure effective service delivery, making motivation and discipline critical factors to investigate. This study examines the influence of motivation and work discipline on employee performance at the Ministry of Religious Affairs Office in South Tangerang City. This research employs a quantitative approach using a survey method. The sampling technique applied is saturated sampling, involving all 60 employees as respondents. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 27. The findings reveal that both motivation and work discipline have positive and significant effects on employee performance, both partially and simultaneously. Work discipline demonstrates a slightly stronger influence compared to motivation. These results indicate that enhancing discipline and motivation can substantially improve employee outcomes. Furthermore, the coefficient of determination suggests that while these variables contribute significantly, other factors such as work environment, workload, and training also play important roles. The implications of this study highlight the need for organizations to strengthen policies, training programs, and supervisory mechanisms to foster higher levels of motivation and discipline. At the same time, organizations should address other supporting factors to achieve optimal employee performance.